CUSTOMER RELATION MANAGEMENT PADA KLINIK ESTETIKA SEMARANG MENGGUNAKAN SMS GATEWAY (Information Technology and Telematics, 2015)
Abstract-- In the development of any business maintaining a good relationship with customers is something that needs to be done , especially a company engaged in the field of skin health as ESTETIKA Clinic dr . Affandi Semarang . Besides selling drug products for skin care , Clinic ESTETIKA dr . Affandi Semarang provide skin care services through the treatment - specific treatment .                    Through SMS Gateway Clinic ESTETIKA dr . Affandi Semarang want to provide more optimal services with particular regard to promo information , check the schedule reminders , schedule doctor's newest and birthday greeting . This research aims to design and build a CRM application using SMS Gateway which will be implemented on ESTETIKA Clinic dr . Affandi Semarang . Keywords-- Customer Relationship Management ( CRM ) , SMS Gateway , ESTETIKA Clinic dr . Affandi Semarang .